PENGARUH BUDAYA ORGANISASI, KOMITMEN KARYAWAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. DENDYMARKER INDAH LESTARI DI LUBUK LINGGAU - REZA ADITYA HIDAYAT; Trisniarty Adjengmoelyati; Wani Fitriah (DIBINOM : Digital Business, Economic Jurnal, 2026)
This study aims to determine the Influence of Organizational Culture, Employee Commitment and Work Discipline on Employee Performance of PT. Dendymarker Indah Lestari in Lubuk Linggau. This type of research is associative research. The data collection technique used is to distribute questionnaires. The research population was 90 employees. The number of samples in this study is 74. The data analysis used is qualitative and quantitative. The analytical methods applied are multiple linear regression analysis, F-test, t-test and coefficient of determination. The results of the study show the influence of Organizational Culture, Employee Commitment and Work Discipline on Employee Performance. This is evidenced by the results of multiple linear regression. Simultaneously showing a positive and significant influence of Organizational Culture and Work Discipline on Employee Performance with a Ftcal value (36.451) > Ftable of 2.78 with a significant 0.000 < 0.05. As Organizational Culture affects employee performance with a tcal value (3.568) > ttable (1.666) with a significant t of 0.001 < 0.05. Employee Commitment has a significant influence on Employee Performance with a tcal value (3.779) > ttable (1.666) with a significant t of 0.000 < 0.05. Work Discipline has a significant influence on Employee Performance with a tcal value (5.512) > ttable (1.666) with a significant t of 0.000 < 0.05. The determination of the 0.593 (59.3%) variable Organizational Culture and Work Discipline was able to explain performance. While the remaining 40.7% were influenced by other factors outside the study